Outcome Mapping (Better Evaluation, 2013)
Outcome mapping (OM) is a methodology for planning, monitoring and eva luating development initiatives in order to bring about sustainable so cial change. As the name suggests, its niche is understanding outcomes ; the so-called ‘missing-middle’ or ‘black box’ of results that emerge downstream from the initiative’s activities but upstream from longer- term economic, environmental, political or demographic changes. At the planning stage, the process of outcome mapping helps a project team o r program be specific about the actors it intends to target, the chang es it hopes to see and the strategies appropriate to achieve these. Fo r ongoing monitoring, OM provides a set of tools to design and gather information on the results of the change process, measured in terms of the changes in behaviour, actions or relationships that can be influe nced by the team or program.